2018
DOI: 10.1038/s41598-018-28455-1
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic carbon and nitrogen assimilation in cellular compartments of a benthic kleptoplastic foraminifer

Abstract: Haynesina germanica, an ubiquitous benthic foraminifer in intertidal mudflats, has the remarkable ability to isolate, sequester, and use chloroplasts from microalgae. The photosynthetic functionality of these kleptoplasts has been demonstrated by measuring photosystem II quantum efficiency and O2 production rates, but the precise role of the kleptoplasts in foraminiferal metabolism is poorly understood. Thus, the mechanism and dynamics of C and N assimilation and translocation from the kleptoplasts to the fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 71 publications
1
52
0
Order By: Relevance
“…In intertidal kleptoplastidic foraminiferal species, oxygenic photosynthesis was found to be functional and inorganic carbon assimilation was demonstrated (Lopez, ; LeKieffre et al ., ). However, below the photic limit, which typically does not exceed 15–20 m in the Gullmar Fjord during the season we sampled (Erlandsson and Stigebrandt, ), it is unlikely that oxygenic photosynthesis would occur.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In intertidal kleptoplastidic foraminiferal species, oxygenic photosynthesis was found to be functional and inorganic carbon assimilation was demonstrated (Lopez, ; LeKieffre et al ., ). However, below the photic limit, which typically does not exceed 15–20 m in the Gullmar Fjord during the season we sampled (Erlandsson and Stigebrandt, ), it is unlikely that oxygenic photosynthesis would occur.…”
Section: Discussionmentioning
confidence: 98%
“…We combined ultrastructural analyses, which were executed with a transmission electron microscope (TEM), correlated with nanometre scale secondary ion mass spectrometry (NanoSIMS) imaging (Hoppe et al ., ; Nuñez et al ., ) to localize isotopically labelled 15 N, 13 C and 34 S compounds at a sub‐cellular level and to correlate the elemental isotopic composition with ultrastructural features of N. labradorica . This TEM‐NanoSIMS analysis has revealed the fate of isotopically labelled compounds in diverse marine microorganisms (Finzi‐Hart et al ., ; Pernice et al ., ; Kopp et al ., ; ; Raina et al ., ), including foraminifera (Nomaki et al ., ; LeKieffre et al ., ; ). Additionally, microelectrodes were used to determine the oxygen dynamics around N. labradorica as a function of artificial light exposure (Rink et al ., ; Geslin et al ., ), in order to link C and N assimilation with potential photosynthetic activity.…”
Section: Introductionmentioning
confidence: 98%
“…This is due to the fact that every probe may have affinity to different epitopes of Factin, therefore, may not label all different F-actin-containing structures equally. The effectiveness of staining F-actin using different probes was compared by Lemieux et al (2014). They reported that different probes did not stain all subsets of F-actin equally.…”
Section: Previous Studies Of Actin In Foraminifera Using Fluorescent mentioning
confidence: 99%
“…Although the chemical composition of FV is uncertain we can assume from a high content of nitrogen (LeKieffre et al, 2018b) that they likely contain proteins. Internal material contained within FV appears to have a specific 3D net-like nanostructure.…”
Section: Fibrillar Vesiclesmentioning
confidence: 99%